Toner and method for producing toner

By using crystalline resins of specific polymeric monomers in the toner, the monomer ratio and crosslink density of the polymer are controlled, and the problems of uneven image density and development in high-speed printing equipment are solved, thereby achieving efficient low-temperature fixing and heat resistance storage stability.

CN110597029BActive Publication Date: 2025-01-03CANON KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201910507003.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-04-10
Filing Date
2019-06-12
Publication Date
2025-01-03
Estimated Expiration
2039-06-12

AI Technical Summary

Technical Problem

In high-speed printing equipment, it is difficult for the existing toner to meet the requirements of low-temperature fixability, heat resistance storage stability, image density uniformity and development properties at the same time, especially in high-speed machines, the problem of image density unevenness and development properties is likely to occur.

Method used

The crystalline resin containing a specific polymerizable monomer is used as the binder resin. By controlling the monomer ratio and crosslinking density in the polymer, the storage elastic modulus of the toner at 150°C reaches 1.0×104Pa or more. And a clear phase separation state is formed in the polymer to maintain the melting point, meet the low-temperature fixing and heat-resistant storage stability, and optimize the development.

Benefits of technology

It realizes a high level of image density uniformity and development in high-speed printing equipment, while maintaining excellent heat-resistant storage stability and low-temperature fixing, solving the problems of image density unevenness and development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002092152180000101
    Figure BDA0002092152180000101
  • Figure BDA0002092152180000111
    Figure BDA0002092152180000111
  • Figure BDA0002092152180000281
    Figure BDA0002092152180000281
Patent Text Reader

Abstract

The present invention relates to a toner and a method for producing the toner. A toner comprising toner particles containing a binder resin, wherein the toner has a storage elastic modulus Gt'(150) of 1.0×10 4 Pa or above, the binder resin includes a polymer A having a first monomer unit derived from a first polymerizable monomer and a second monomer unit derived from a second polymerizable monomer different from the first polymerizable monomer, the first polymerizable monomer is selected from a specific (meth)acrylate, the content of the first monomer unit and the second monomer unit in the polymer A is within a specific range, and the SP values ​​of the first monomer unit and the second monomer unit are within a specific range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a toner used in electrophotography, electrostatic recording, magnetic recording, etc., and a method for producing the toner. Background Art

[0002] Recently, higher printing speeds are required in electrophotographic apparatuses. This requirement is increasing year by year, and for the purpose of reducing the fixing time, the low-temperature fixing property of toner is being improved.

[0003] In order to improve low-temperature fixability, a method for lowering the glass transition temperature of a non-crystalline binder resin as a main component of a general toner has been proposed. However, since heat-resistant storage stability decreases when the glass transition temperature is lowered, a toner having a low glass transition temperature designed to meet the requirements of low-temperature fixability has a problem of insufficient heat-resistant storage stability during long-term storage and transportation at high temperatures.

[0004] Therefore, crystalline resins have been studied as binder resins that can provide both low-temperature fixability and heat-resistant storage stability. Unlike non-crystalline resins, crystalline resins do not have a clear glass transition point and have the property of not changing their state before the melting point. In addition, since they form a regular molecular arrangement, they have a rapid melting property of rapidly melting at the melting point. Therefore, they have the characteristics of being able to provide both heat-resistant storage stability and low-temperature fixability.

[0005] For example, as an improvement in obtaining sharp melting properties, Japanese Patent Application Laid-Open No. 2014-130243 proposes using a crystalline vinyl resin obtained by copolymerizing a polymerizable monomer having a long-chain alkyl group and a non-crystalline polymerizable monomer as a binder resin of a toner.

[0006] Japanese Patent Application Laid-Open No. 2003-107774 proposes improving unevenness in image density during fixing by using a three-dimensionally crosslinked resin as a binder resin. Summary of the invention

[0007] However, when the rapid melting property is improved by using a large amount of crystalline vinyl resin as in Japanese Patent Application Laid-Open No. 2014-130243, a small temperature change leads to a large change in the melting state of the toner. As a result, it has been found that the problem of uneven image density during fixing is more likely to occur in a high-speed machine. It is believed that this is because the time spent passing through the fixing unit is short in a high-speed machine, and therefore the temperature received by the toner is greatly affected by the unevenness of the paper.

[0008] Problems with developability are also found in high-speed machines, where the image density decreases when printing an image with a large amount of toner, as in the case of an overall solid image. This is thought to be because charge leakage may occur due to reduced current density in the crystalline site, so the toner as a whole cannot be sufficiently charged.

[0009] On the other hand, although the image density unevenness is improved to some extent by the method of Japanese Patent Application Laid-Open No. 2003-107774, it is still found to be insufficient when a three-dimensional crosslinked resin is used together with a crystalline resin. This is considered to be because crystalline sites and insoluble sites are unevenly present in the toner during melting. Moreover, this still does not solve the density problem of the overall solid image.

[0010] Therefore, it is extremely difficult to satisfy all the requirements of developability and image density unevenness while also improving heat-resistant storage stability and low-temperature fixing property.

[0011] The present invention provides a toner having excellent heat-resistant storage stability and low-temperature fixing property and capable of providing high levels of image density uniformity and developing property.

[0012] A first embodiment of the present invention is directed to a toner comprising toner particles containing a binder resin, wherein

[0013] The storage elastic modulus Gt'(150) of the toner at 150°C is 1.0×10 4 Pa or above,

[0014] The binder resin includes a polymer A having a first monomer unit derived from a first polymerizable monomer and a second monomer unit derived from a second polymerizable monomer different from the first polymerizable monomer,

[0015] The first polymerizable monomer is selected from the group consisting of 18-36 At least one of the group consisting of alkyl (meth)acrylates,

[0016] The content of the first monomer unit in polymer A is 5.0 mol% to 60.0 mol% of the total molar number of all monomer units in polymer A.

[0017] The content of the second monomer unit in polymer A is 20.0 mol% to 95.0 mol% of the total moles of all monomer units in polymer A, and

[0018] When the SP value of the first monomer unit is SP 11 (J / cm 3 ) 0.5 , and the SP value of the second monomer unit is SP 21 (J / cm 3 ) 0.5When , the following formula (1) is satisfied:

[0019] 3.00≤(SP 21 -SP 11 )≤25.00 (1).

[0020] A second embodiment of the present invention is directed to a toner comprising toner particles containing a binder resin, wherein

[0021] The storage elastic modulus Gt'(150) of the toner at 150°C is 1.0×10 4 Pa or above,

[0022] The binder resin includes a polymer A which is a polymer of a composition including a first polymerizable monomer and a second polymerizable monomer different from the first polymerizable monomer,

[0023] The first polymerizable monomer is selected from the group consisting of 18-36 At least one of the group consisting of alkyl (meth)acrylates,

[0024] The content of the first polymerizable monomer in the composition is 5.0 mol% to 60.0 mol% of the total moles of all polymerizable monomers in the composition.

[0025] The content of the second polymerizable monomer in the composition is 20.0 mol% to 95.0 mol% of the total moles of all polymerizable monomers in the composition, and

[0026] When the SP value of the first polymerizable monomer is SP 12 (J / cm 3 ) 0.5 , and the SP value of the second polymerizable monomer is SP 22 (J / cm 3 ) 0.5 When , the following formula (2) is satisfied:

[0027] 0.60≤(SP 22 -SP 12 )≤15.00 (2).

[0028] The present invention can provide a toner having excellent heat-resistant storage stability and low-temperature fixability while providing both image density uniformity and developability at high levels.

[0029] Further features of the present invention will become apparent from the following description of exemplary embodiments. DETAILED DESCRIPTION

[0030] Unless otherwise specified, the description of a numerical range such as "A or more and B or less" or "A to B" in the present invention includes the numerical values ​​of the upper limit and the lower limit of the range.

[0031] In the present invention, (meth)acrylate refers to acrylate and / or methacrylate.

[0032] In the present invention, "monomer unit" refers to the reacted form of a monomeric species in a polymer.

[0033] The crystalline resin is a resin showing a clear endothermic peak in differential scanning calorimetry (DSC).

[0034] In order to give the toner both rapid melting property and heat-resistant storage stability, it is effective to use a crystalline resin as the main component of the binder resin in the toner. However, when the crystalline resin is the main component, it inhibits charging during development and adversely affects uniform wet diffusion during fixing.

[0035] Therefore, in the toner with low temperature fixability and heat resistant storage stability, it is necessary to improve the developability and image density uniformity during fixing. However, it is not easy to achieve all of this. Of course, by including a large amount of materials such as crystalline resins or low melting point waxes, it is possible to improve the heat resistant storage stability while promoting rapid melting. However, since such materials have low resistance, they may cause problems with the developability of the toner in the electrophotographic system. In addition, when emphasizing rapid melting, the molten state of the toner may be affected by small temperature changes.

[0036] In view of these problems, we have found that in the present invention, it is possible to achieve developability while providing low temperature fixability and heat resistant storage stability at a high level. The toner of the present invention can be used in higher speed machines and also has good image density uniformity during fixing, which is a trade-off with low temperature fixability.

[0037] In the present invention, the storage elastic modulus Gt'(150) of the toner at 150°C must be 1.0×10 4 Pa or above.

[0038] When the toner is exposed to just enough heat to melt it from the outside, its viscoelasticity naturally decreases, but the storage elastic modulus is thought to maintain a constant value at high temperatures because the insoluble components of the toner maintain a constant viscoelasticity of the toner as a whole.

[0039] If the storage elastic modulus of the toner is high at high temperature, the image density unevenness during fixing can be good, so the value of the storage elastic modulus at 150° C. must be 1.0×10 4 Pa or more, and preferably 2.0×10 4 Pa or more, or more preferably 2.7×10 4 Pa or more. There is no particular upper limit, but it is preferably 1.0×107 Pa or less, or more preferably 1.0×10 6 Pa or less. This value can be controlled by controlling the molecular weight and crosslinking density of the binder resin.

[0040] In the first embodiment of the present invention, the binder resin comprises a polymer A having a first monomer unit derived from a first polymerizable monomer and a second monomer unit derived from a second polymerizable monomer different from the first polymerizable monomer. In addition, the first polymerizable monomer is selected from 18-36 At least one of the group consisting of (meth)acrylates of alkyl groups, and the content of the first monomer unit in polymer A is 5.0 mol% to 60.0 mol% of the total moles of all monomer units in polymer A, and the content of the second monomer unit in polymer A is 20.0 mol% to 95.0 mol% of the total moles of all monomer units in polymer A. In addition, when the SP value of the first monomer unit is SP 11 (J / cm 3 ) 0.5 , and the SP value of the second monomer unit is SP 21 (J / cm 3 ) 0.5 When , the following formula (1) is satisfied:

[0041] 3.00≤(SP 21 -SP 11 )≤25.00 (1).

[0042] In a second embodiment of the present invention, the binder resin includes a polymer A which is a polymer of a composition including a first polymerizable monomer and a second polymerizable monomer different from the first polymerizable monomer. The first polymerizable monomer is selected from the group consisting of 18-36 At least one of the group consisting of (meth)acrylates of alkyl groups, the content of the first polymerizable monomer in the composition is 5.0 mol% to 60.0 mol% of the total moles of all polymerizable monomers in the composition, and the content of the second polymerizable monomer in the composition is 20.0 mol% to 95.0 mol% of the total moles of all polymerizable monomers in the composition. In addition, when the SP value of the first polymerizable monomer is SP 12 (J / cm 3 ) 0.5 , and the SP value of the second polymerizable monomer is SP 22 (J / cm 3 ) 0.5 When , the following formula (2) is satisfied:

[0043] 0.60≤(SP 22 -SP 12 )≤15.00 (2).

[0044] Here, the "SP" value is an abbreviation for solubility parameter and is used as an indicator of solubility. The calculation method is as follows.

[0045] The SP value in the present invention is expressed as (J / m 3 ) 0.5 The units are given, but the formula 1 (cal / cm 3 ) 0.5 =2.045×10 3 (J / m 3 ) 0.5 Convert it to (cal / cm 3 ) 0.5 Unit of.

[0046] In the present invention, SP 21 -SP 11 The value of is 3.00 to 25.00, or preferably 5.00 to 22.00, or more preferably 6.00 to 20.00.

[0047] In a second embodiment, SP 22 -SP 12 The value of is 0.60 to 15.00, or preferably 3.00 to 12.00.

[0048] If the above conditions are satisfied, the melting point is maintained without reducing the crystallinity of the polymer A. Therefore, both low-temperature fixability and heat-resistant storage stability can be achieved. The mechanism is considered to be as follows.

[0049] When the first monomer unit is introduced into the polymer A and the first monomer units are aggregated together, crystallinity is exhibited, but generally, since crystallization is suppressed by introducing other monomer units, it is difficult to exhibit crystallinity in the polymer. This tendency is particularly significant when the first monomer unit and other monomer units are randomly bonded in a single molecule of the polymer.

[0050] However, in the present invention, it is considered that the use of polymer A makes SP 22 -SP 12 The polymerizable monomers in the above range are composed, or the SP 21 -SP 11 The monomer units are composed within the above range, so the first polymerizable monomer and the second polymerizable monomer can be continuously bonded to a certain extent during polymerization rather than randomly bonded. Therefore, the first monomer units can be aggregated in polymer A, and even if other monomer units are introduced, the melting point can be maintained because the crystallinity can be improved.

[0051] In addition, it is considered that if SP 21 -SP 11Within the above range, a clear phase separation state can be formed in the polymer A without mutual dissolution of the first monomer unit and the second monomer unit, so that the crystallinity is not reduced and the melting point is maintained.

[0052] The polymer A preferably has a crystalline part including a first monomer unit derived from a first polymerizable monomer. The polymer A also preferably has a non-crystalline part including a second monomer unit derived from a second polymerizable monomer.

[0053] If SP 22 -SP 12 Less than 0.60, the melting point of polymer A decreases, and heat-resistant storage stability decreases. On the other hand, if it exceeds 15.00, it is considered that the copolymerizability of polymer A will be poor, resulting in non-uniformization and a decrease in low-temperature fixability.

[0054] Similarly, if SP 21 -SP 11 Less than 3.00, the melting point of polymer A decreases, and heat-resistant storage stability decreases. On the other hand, if it exceeds 25.00, it is considered that the copolymerizability of polymer A will be poor, resulting in non-uniformization and a decrease in low-temperature fixability.

[0055] It is important that the first polymerizable monomer is selected from the group consisting of (preferably linear) C 18-36 At least one of the group consisting of (meth)acrylates of alkyl groups. If the first polymerizable monomer is a specific (meth)acrylate, the polymer A has crystallinity and can improve low-temperature fixability and storability by virtue of rapid melting.

[0056] From the viewpoint of improving low-temperature fixing property, the first polymerizable monomer is preferably at least one selected from the group consisting of (meth)acrylates having a (preferably linear) alkyl group of 30 or less carbon atoms. From the viewpoint of improving storage property, the first polymerizable monomer is preferably at least one selected from the group consisting of (meth)acrylates having a (preferably linear) alkyl group of 22 or more carbon atoms.

[0057] Furthermore, in the first embodiment, the content of the first monomer unit in the polymer A is 5.0 mol% to 60.0 mol% of the total moles of all monomer units in the polymer A.

[0058] In a second embodiment, the content of the first polymerizable monomer in the composition is 5.0 mol% to 60.0 mol% of the total moles of all polymerizable monomers in the composition.

[0059] The content of the first monomer unit or the first polymerizable monomer is preferably 10.0 mol% to 60.0 mol%, or more preferably 20.0 mol% to 40.0 mol%. If the content is within this range, the crystalline part of the toner shows good sharp melting property, and low temperature fixing property is improved.

[0060] Furthermore, in the first embodiment, the content of the second monomer unit in polymer A is 20.0 mol% to 95.0 mol% of the total moles of all monomer units in polymer A. In the second embodiment, the content of the second polymerizable monomer in the composition is 20.0 mol% to 95.0 mol% of the total moles of all polymerizable monomers in the composition.

[0061] The content of the second monomer unit or the second polymerizable monomer is preferably 40.0 mol% to 95.0 mol%, or more preferably 40.0 mol% to 70.0 mol%. If the content is within this range, the crystallinity of the first monomer unit in the polymer A is improved, resulting in good low-temperature fixability and storability.

[0062] In addition to the first monomer unit and the second monomer unit, a third monomer unit derived from a third polymerizable monomer outside the range of either of the above formula (1) or (2) may also be contained in the polymer A. In this case, in the first embodiment, when the SP value of the third monomer unit is SP 31 (J / cm 3 ) 0.5 When 31 SP is preferred 11 Above but less than SP 21 In the second embodiment, when the SP value of the third polymerizable monomer is SP 32 (J / cm 3 ) 0.5 When 32 SP is preferred 12 Above but less than SP 22 Within this range, the crystallinity of the first monomer unit in the polymer A is improved, resulting in good storability.

[0063] It is important that the first polymerizable monomer is selected from 18-36 At least one member selected from the group consisting of alkyl (meth)acrylates.

[0064] With C 18-36 Examples of alkyl (meth)acrylates include 18-36(Meth)acrylates of linear alkyl groups [stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosyl (meth)acrylate, behenyl (meth)acrylate, lauryl (meth)acrylate, ceryl (meth)acrylate, dioctadecyl (meth)acrylate, myricyl (meth)acrylate, tridecyl (meth)acrylate, etc.] and those having C 18-36 Branched alkyl (meth)acrylates [2-decyltetradecyl (meth)acrylate, etc.].

[0065] Among them, selected from the group having C 18-36 At least one of the group consisting of (meth)acrylates of linear alkyl groups is preferred, selected from the group consisting of (meth)acrylates having C 18-30 At least one kind selected from the group consisting of linear alkyl (meth)acrylates is more preferred, and at least one kind selected from the group consisting of linear stearyl (meth)acrylate and behenyl (meth)acrylate is still more preferred.

[0066] As the first polymerizable monomer, one monomer may be used alone or two or more monomers may be used in combination.

[0067] For example, among those given below, a polymerizable monomer conforming to formula (1) or (2) can be used as the second polymerizable monomer. As the second polymerizable monomer, one monomer may be used alone, or two or more monomers may be used in combination.

[0068] Monomers having a nitrile group: for example, acrylonitrile, methacrylonitrile, and the like.

[0069] Monomers having a hydroxyl group: for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and the like.

[0070] Monomers having an acylamino group: for example, acrylamide and 1-30 Amines and C 2-30 A monomer obtained by reacting carboxylic acids (acrylic acid, methacrylic acid, etc.).

[0071] Monomers having urethane groups: For example, by reacting C having ethylenically unsaturated bonds with a known method. 2-22 Alcohol (2-hydroxyethyl methacrylate, vinyl alcohol, etc.) and C 1-30Isocyanates [monoisocyanate compounds (benzenesulfonyl isocyanate, toluenesulfonyl isocyanate, phenyl isocyanate, p-chlorophenyl isocyanate, butyl isocyanate, hexyl isocyanate, tert-butyl isocyanate, cyclohexyl isocyanate, octyl isocyanate, 2-ethylhexyl isocyanate, dodecyl isocyanate, adamantyl isocyanate, 2,6-dimethylphenyl isocyanate, 3,5-dimethylphenyl isocyanate, and 2,6-dipropylphenyl isocyanate, etc.), aliphatic diisocyanate compounds (trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate, etc.) , alicyclic diisocyanate compounds (1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate and hydrogenated tetramethylxylylene diisocyanate, etc.) and aromatic diisocyanate compounds (phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-tolyl diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenyl ether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate and xylylene diisocyanate, etc.), and

[0072] By using a known method, C 1-26 Alcohols (methanol, ethanol, propanol, isopropanol, butanol, tert-butanol, amyl alcohol, heptanol, octanol, 2-ethylhexanol, nonanol, decanol, undecanol, lauryl alcohol, dodecanol, myristyl alcohol, pentadecanol, cetyl alcohol, heptadecanol, stearyl alcohol, isostearyl alcohol, oleyl alcohol, linoleyl alcohol, linoleyl alcohol, nonadecanol, heneicosyl alcohol, behenyl alcohol, erucyl alcohol, etc.) and C 2-30 A monomer obtained by reacting isocyanate [2-isocyanatoethyl (meth)acrylate, 2-(0-[1'-methylpropylideneamino]carboxyamino)ethyl (meth)acrylate, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl (meth)acrylate, 1,1-(bis(meth)acryloyloxymethyl)ethyl isocyanate, etc.].

[0073] Monomers having urea groups: For example, by reacting C 3-22 Amines [primary amines (n-butylamine, tert-butylamine, propylamine, isopropylamine, etc.), secondary amines (di-n-ethylamine, di-n-propylamine, di-n-butylamine, etc.), aniline, cyclohexylamine, etc.] and C2-30 Monomers obtained by reaction with isocyanate. Monomers having a carboxyl group: for example, methacrylic acid, acrylic acid, 2-carboxyethyl (meth)acrylate.

[0074] Among them, it is desirable to use a monomer having a nitrile group, an acylamino group, a carbamate group, a hydroxyl group or a urea group. A monomer having an ethylenically unsaturated bond and at least one functional group selected from the group consisting of a nitrile group, an acylamino group, a carbamate group, a hydroxyl group and a urea group is still more preferred.

[0075] As the second polymerizable monomer, vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl decanoate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate and vinyl octylate can also be preferably used.

[0076] Vinyl esters are non-conjugated monomers and can easily maintain moderate reactivity with the first polymerizable monomer, so it becomes easier to improve the crystallinity of the polymer A and better achieve both low-temperature fixability and heat-resistant storage stability.

[0077] The second polymerizable monomer preferably has an ethylenically unsaturated bond, and more preferably has one ethylenically unsaturated bond.

[0078] Furthermore, the second polymerizable monomer is preferably at least one selected from the group consisting of the following formulae (A) and (B).

[0079]

[0080] (In the formula, X represents a single bond or C 1-6 Alkylene, and R 1 represents a nitrile group (-C≡N), an acylamino group (-C(=O)NHR 10 (R 10 A hydrogen atom or C 1-4 Alkyl)), hydroxyl, -COOR 11 (R 11 C 1-6 (Preferably C 1-4 ) alkyl or C 1-6 (Preferably C 1-4 ) hydroxyalkyl), carbamate (-NHCOOR 12 (R 12 C 1-4 alkyl)), urea (-NH-C(=O)-N(R 13 )2(where each R 13 are independently hydrogen atoms or C 1-6 (Preferably C1-4 )alkyl))、-COO(CH2)2NHCOOR 14 (R 14 C 1-4 alkyl) or -COO(CH2)2-NH-C(=O)-N(R 15 )2(where R 15 are independently a hydrogen atom or a C 1-6 (Preferably C 1-4 )alkyl).

[0081] Preferably R 1 is a nitrile group (-C≡N), an acylamino group (-C(=O)NHR 10 (R 10 A hydrogen atom or C 1-4 Alkyl)), hydroxyl, -COOR 11 (R 11 C 1-6 (Preferably C 1-4 ) alkyl or C 1-6 (Preferably C 1-4 ) hydroxyalkyl), urea (-NH-C(=O)-N(R 13 )2(where each R 13 are independently hydrogen atoms or C 1-6 (Preferably C 1-4 )alkyl))、-COO(CH2)2NHCOOR 14 (R 14 C 1-4 alkyl) or -COO(CH2)2-NH-C(=O)-N(R 15 )2(where R 15 are independently a hydrogen atom or a C 1-6 (Preferably C 1-4 )alkyl).

[0082] R 2 C 1-4 Alkyl, and R 3 Each is independently a hydrogen atom or a methyl group.

[0083] The monomer unit in the present invention is defined as a carbon-carbon bonded region in the main chain composed of polymerized vinyl monomers in the polymer.

[0084] The vinyl monomer can be represented by the following formula (A).

[0085]

[0086] [In formula (A), R1 represents a hydrogen atom or an alkyl group (preferably C 1-3alkyl, or more preferably methyl), and R2 represents any optional substituent.]

[0087] When there are multiple monomer units satisfying the conditions of the first monomer unit in the polymer A of the present invention, SP in formula (1) 11 The value of is the weighted average of the SP values ​​of each of these monomer units. For example, if the polymer contains A mol% of the total molar number of monomer units satisfying the condition of the first monomer unit, the SP value is SP 111 The monomer unit A of the first monomer unit, and the SP value based on the total molar number of the monomer units satisfying the condition of the first monomer unit being (100-A) mol% is SP 112 The monomer unit B, then the SP value (SP 11 )for:

[0088] SP 11 =(SP 111 ×A+SP 112 ×(100-A)) / 100.

[0089] When three or more monomer units satisfying the conditions of the first monomer unit are included, the calculation is similar. 12 The average value calculated based on the molar ratio of each first polymerizable monomer is also shown.

[0090] In addition, the second monomer unit in the present invention corresponds to SP satisfying formula (1): 21 The value is the same as the SP calculated by the above method. 11 Similarly, the second polymerizable monomer corresponds to the SP satisfying formula (2): 22 The value is the same as the SP calculated by the above method. 12 Value combination of all polymerizable monomers.

[0091] That is, when the second polymerizable monomer is two or more polymerizable monomers, SP 21 represents the SP value of the monomer unit derived from each polymerizable monomer, and the SP value is determined for the monomer unit derived from each second polymerizable monomer. 21 -SP 11 Similarly, SP 22 represents the SP value of each polymerizable monomer, and determines the SP value for each second polymerizable monomer. 22 -SP 12 .

[0092] Polymer A may also contain a third monomer unit derived from a third polymerizable monomer outside the range of formulae (1) and (2) (i.e., different from the first and second polymerizable monomers), as long as the molar ratio of the first and second monomer units remains within the specified range.

[0093] Examples of the third polymerizable monomer include styrenes such as styrene and o-methylstyrene and their derivatives, and (meth)acrylates such as n-butyl (meth)acrylate, tert-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate.

[0094] In order to improve the storability of the toner, the third polymerizable monomer is preferably at least one selected from the group consisting of styrene, methyl methacrylate, and methyl acrylate.

[0095] The polymer A is preferably a vinyl polymer. The vinyl polymer may be, for example, a polymer of a monomer containing an ethylenically unsaturated bond. The ethylenically unsaturated bond is a carbon-carbon double bond that can be polymerized by free radicals, and examples include vinyl, propylene, acryloyl, methacryloyl, and the like.

[0096] The content of the first monomer unit in polymer A is preferably 7 mol% or more of the total monomer units in the binder resin, or more preferably 15 mol% or more. There is no particular upper limit, but preferably the content is 80 mol% or less, or more preferably 60 mol% or less. If the first monomer unit in polymer A is contained in the binder resin in this amount, the low-temperature fixability is good because the rapid melting property is improved.

[0097] The acid value of polymer A is preferably 30.0 mgKOH / g or less, or more preferably 20.0 mgKOH / g or less. There is no particular lower limit, but it is preferably 0 mgKOH / g or more. If the acid value is 30.0 mgKOH / g or less, it is less likely to inhibit the crystallization of polymer A, so a good melting point is maintained.

[0098] The weight average molecular weight (Mw) of the tetrahydrofuran (THF) soluble component of the polymer A measured by gel permeation chromatography is preferably 8,000 to 200,000, or more preferably 12,000 to 100,000. If the Mw is within this range, good brittleness of the toner at around room temperature is obtained.

[0099] The melting point of the polymer A is preferably 50° C. to 80° C., or more preferably 53° C. to 70° C. If the melting point of the polymer A is within this range, good heat-resistant storage stability and low-temperature fixing property are obtained.

[0100] The binder resin contained in the toner particles preferably contains a polymer B different from a polymer A.

[0101] Examples of polymer B include vinyl resins, polyester resins, epoxy resins, and polyurethane resins. For the purpose of controlling viscoelasticity at high temperatures, it is particularly desirable to include a vinyl resin or a polyester resin so that the crosslinking density can be more easily controlled. In order to achieve good dispersibility of polymer B in toner, it is particularly desirable to include a polyester resin having an SP value close to that of the non-crystalline portion of polymer A.

[0102] From the viewpoint of heat-resistant storage stability, the glass transition temperature (Tg) of the polymer B is preferably 55° C. or higher, or more preferably 60° C. or higher, or still more preferably 65° C. or higher. From the viewpoint of not inhibiting the low-temperature fixing property of the polymer A, the glass transition temperature (Tg) is preferably 90° C. or lower, or more preferably 80° C. or lower.

[0103] The content of the polymer A in the binder resin is preferably 40% by mass to 100% by mass, or more preferably 50% by mass to 90% by mass.

[0104] The content of the polymer B in the binder resin is preferably 0% by mass to 60% by mass, or more preferably 10% by mass to 50% by mass.

[0105] Examples of the polymerizable monomer that can be used for the vinyl resin include polymerizable monomers that can be used as the above-mentioned first polymerizable monomer, second polymerizable monomer, and third polymerizable monomer. Two or more thereof may be used in combination as necessary.

[0106] When a vinyl resin is used for polymer B, the vinyl resin preferably has a crosslinked structure obtained by crosslinking with a crosslinking agent having two or more vinyl groups. Examples of the crosslinking agent used in this case include the following:

[0107] Aromatic divinyl compounds (divinylbenzene, divinylnaphthalene); diacrylate compounds linked by an alkyl chain (ethylene glycol diacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, and these compounds with methacrylate instead of acrylate); diacrylate compounds linked by an alkyl chain containing an ether bond (for example, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, esters, polyethylene glycol #400 diacrylate, polyethylene glycol #600 diacrylate, dipropylene glycol diacrylate, and these compounds with methacrylate instead of acrylate); diacrylate compounds linked by a chain containing an aromatic group and an ether bond [polyoxyethylene (2)-2,2-bis(4-hydroxyphenyl)propane diacrylate, polyoxyethylene (4)-2,2-bis(4-hydroxyphenyl)propane diacrylate, and these compounds with methacrylate instead of acrylate]; and polyester diacrylate compounds.

[0108] The following are examples of the polyfunctional crosslinking agent: pentaerythritol triacrylate, trimethylolethane triacrylate, trimethylolpropane triacrylate, tetramethylolmethane tetraacrylate, oligoester acrylates, and these compounds with methacrylates instead of acrylates; and triallyl cyanurate and triallyl trimellitate.

[0109] These crosslinking agents are used in an amount of preferably 0.01 to 10.00 parts by mass, or more preferably 0.03 to 5.00 parts by mass relative to 100 parts by mass of the monomer components other than the crosslinking agent.

[0110] Among these crosslinking agents, aromatic divinyl compounds (particularly divinylbenzene) and diacrylate compounds linked through a chain containing an aromatic group and an ether bond are examples of crosslinking agents that can be favorably used from the viewpoint of the anti-offset property and fixability of the binder resin.

[0111] Furthermore, the polymer B preferably contains a polyester resin having a monomer unit derived from a polyhydric alcohol and a monomer unit derived from a polycarboxylic acid. If the polymer B contains a polyester resin, initial developability is good.

[0112] The authors believe that since the SP value of polymer B is close to the SP value of the second monomer unit of polymer A and polymer A and polymer B are very close, there are fewer aggregated portions of polymer A units, resulting in suppressed charge leakage.

[0113] Examples of polycarboxylic acids include the following compounds: dibasic acids such as succinic acid, adipic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, malonic acid and dodecenylsuccinic acid, and their anhydrides and lower alkyl esters, and aliphatic unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid and citraconic acid; and 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, and their anhydrides and lower alkyl esters. One of them may be used alone, or two or more thereof may be used in combination.

[0114] Examples of the polyol include the following compounds: alkylene glycols (ethylene glycol, 1,2-propylene glycol and 1,3-propylene glycol); alkylene ether glycols (polyethylene glycol and polypropylene glycol); alicyclic diols (1,4-cyclohexanedimethanol); bisphenols (bisphenol A); and alkylene oxide (ethylene oxide and propylene oxide) adducts of alicyclic diols or bisphenols.

[0115] The alkyl moieties of the alkylene glycol and the alkylene ether glycol may be linear or branched. Other examples include glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol. One of them may be used alone, or two or more thereof may be used in combination.

[0116] If necessary, the acid value or the hydroxyl value may be adjusted by using a monobasic acid such as acetic acid or benzoic acid, or a monohydric alcohol such as cyclohexanol or benzyl alcohol.

[0117] Furthermore, in the first embodiment, it is preferred that the polymer B comprises a polyester resin having a monomer unit derived from a polyol and a monomer unit derived from a polycarboxylic acid, and when the SP value of the monomer unit derived from the polycarboxylic acid is SP 41 (J / cm 3 ) 0.5 When , the following formula (3) is preferably satisfied, or the following formula (3)' is more preferably satisfied.

[0118] 0.0≤|(SP 41 -SP 21 )|≤6.5 (3)

[0119] 0.0≤|(SP 41 -SP 21 )|≤5.5 (3)'

[0120] In the second embodiment, preferably, polymer B comprises a polyester resin having monomer units derived from a polyol and monomer units derived from a polycarboxylic acid, and when the SP value of the polycarboxylic acid is SP 42 (J / cm 3 ) 0.5 When , the following formula (4) is preferably satisfied, or the following formula (4)' is more preferably satisfied.

[0121] 0.0≤|(SP 42 -SP 22 )|≤6.0 (4)

[0122] 0.0≤|(SP 42 -SP 22 )|≤5.0 (4)'

[0123] It is believed that if the difference in SP value is within this range, polymer B shows hydrophilicity close to the second monomer unit of polymer A, and polymer A and polymer B are more likely to be very close. The authors believe that this reduces the aggregation part between the first monomer units of polymer A, thereby suppressing charge leakage.

[0124] The crosslinking agent can also be used to three-dimensionally crosslink the polyester resin of the polymer B. The crosslinking agent is not particularly limited, but is preferably a trivalent or higher polycarboxylic acid, a trivalent or higher polyol, or a derivative thereof.

[0125] Examples of the trivalent or higher polyol component include sorbitol, 1,2,3,6-hexanetetraol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, 2-methylglycerol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxybenzene.

[0126] Examples of the trivalent or higher polycarboxylic acid component include trimellitic acid, pyromellitic acid, 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxy-2-methyl-2-methylenecarboxypropane, tetrakis(methylenecarboxy)methane, 1,2,7,8-octanetetracarboxylic acid, Empol trimer, and anhydrides thereof.

[0127] Among them, trimellitic acid and / or trimellitic anhydride is desirable because it is more reactive as a cross-linking agent and can more easily form a uniform cross-linked structure.

[0128] The binder resin also preferably contains a tetrahydrofuran-insoluble component in an amount of 5% by mass or more, or more preferably 10% by mass or more. There is no particular upper limit, but preferably the content is 40% by mass or less, or preferably 20% by mass or less.

[0129] If the content of the THF insoluble component in the binder resin is within this range, the uneven image density during fixing can be improved. It is believed that this is because the insoluble component can be present in the entire toner particle, so the viscoelasticity of the toner can be maintained above a certain level at high temperatures. The amount of the THF insoluble component can be controlled by controlling the crosslinking density of the polymer B.

[0130] In the measurement of molecular weight distribution of tetrahydrofuran soluble components of the toner, the weight average molecular weight is preferably 30,000 or more, or more preferably 40,000 or more. There is no particular upper limit, but it is preferably 200,000 or less, or more preferably 100,000 or less.

[0131] If the molecular weight is within this range, the first monomer unit in the polymer A becomes less compatible with the polymer B, resulting in good fixing unevenness since the toner melts uniformly as a whole when heated.

[0132] Furthermore, in the viscoelasticity measurement of the tetrahydrofuran-soluble component of the toner, the storage elastic modulus Gk'(50) at 50° C. preferably conforms to the following formula (5):

[0133] Gk'(50)≥1.0×107 Pa (5).

[0134] Gk'(50) is more preferably 1.5×10 7 Pa or more, or more preferably 2.0×10 7 Pa or more. There is no particular upper limit, but it is preferably 1.0×10 10 Pa or less, or more preferably 1.0×10 9 Below Pa.

[0135] If Gk'(50) is within this range, the melting point and glass transition point of the toner are satisfactory, and storage stability is improved. Gk'(50) can be controlled by controlling the molecular weight of the binder resin.

[0136] Furthermore, in the viscoelasticity measurement of the tetrahydrofuran-soluble component of the toner, the storage elastic modulus Gk'(100) at 100° C. preferably conforms to the following formula (6):

[0137] Gk'(100)≤1.0×10 4 Pa (6).

[0138] Gk'(100) is more preferably 0.9×10 4 Pa or less, or more preferably 0.8×10 4 Pa or less. There is no particular lower limit, but it is preferably 1.0×10 2 Pa or more, or more preferably 1.0×10 3 Pa or above.

[0139] When Gk'(100) is within this range, the sharp melting property is excellent and the low-temperature fixability is good. Gk'(100) can be controlled by controlling the amount of the first monomer unit in the polymer A, and the like.

[0140] In addition, in the DSC measurement of the tetrahydrofuran-insoluble component of the toner, the endothermic amount is preferably 4.0 J / g or less, or more preferably 3.5 J / g or less, or still more preferably 2.0 J / g or less. There is no particular lower limit, but it is preferably 0 J / g or more. The lower the endothermic amount, the better. The endothermic amount can be controlled by controlling the crosslinking density of the polymer A.

[0141] If the endothermic value of the tetrahydrofuran insoluble component is within this range, the developability is improved. It is believed that this is because the first monomer unit in polymer A becomes less compatible with polymer B, so that the charging property is maintained in a uniform state. In addition, since the THF insoluble component is no longer plasticized, the image unevenness during fixing is reduced.

[0142] Materials other than the binder resin used for the toner particles are described in detail.

[0143] The toner may also be used as a magnetic toner containing magnetic iron oxide particles. In this case, the magnetic iron oxide particles also serve as a colorant.

[0144] Examples of magnetic iron oxide particles include iron oxides such as magnetite, hematite and ferrite, metals such as iron, cobalt and nickel, or alloys of these metals with other metals such as aluminum, cobalt, copper, lead, magnesium, tin, zinc, antimony, bismuth, calcium, manganese, titanium, tungsten and vanadium, and mixtures thereof.

[0145] The average particle size of these magnetic iron oxide particles is preferably 2 μm or less, or more preferably 0.05 μm to 0.5 μm. The content in the toner is preferably 20 to 200 parts by mass, or more preferably 40 to 150 parts by mass relative to 100 parts by mass of the binder resin.

[0146] A colorant may also be used in the toner. Examples of the colorant are given below.

[0147] As the black colorant, carbon black, grafted carbon, and black obtained by blending the following yellow, magenta, and cyan colorants may be used.

[0148] Typical examples of yellow colorants include condensed azo compounds, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Examples of magenta colorants include condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Examples of cyan colorants include copper phthalocyanine compounds and derivatives thereof, anthraquinone compounds, and basic dye lake compounds.

[0149] These colorants can be used alone, in a mixture, or in a solid solution. The colorant is selected based on considerations of hue angle, chromaticity, brightness, weatherability, OHP transparency, and dispersibility in the toner. The content of the colorant is preferably 1 to 20 parts by mass relative to 100.0 parts by mass of the binder resin.

[0150] Wax may also be contained in the toner to impart release properties during fixing. Examples of the wax include polyolefin copolymers such as polyolefin wax, microcrystalline wax, aliphatic hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax, and ester waxes.

[0151] The content of the wax is preferably 1.0 to 30.0 parts by mass relative to 100.0 parts by mass of the binder resin.

[0152] A charge control agent may be contained in the toner to stabilize triboelectric chargeability. Examples of the charge control agent include those that impart negative chargeability to the toner and those that impart positive chargeability to the toner, and one or two or more of the various charge control agents may be selected according to the type and purpose of the toner.

[0153] Examples of charge control agents for imparting negative chargeability to toners include organic metal complexes (monoazo metal complexes, acetylacetone metal complexes), and metal salts or metal complexes of aromatic hydroxycarboxylic acids or aromatic dicarboxylic acids. Other examples include aromatic monocarboxylic acids and polycarboxylic acids, and their metal salts and anhydrides; and esters and phenol derivatives such as bisphenol.

[0154] Examples of charge control agents for imparting positive chargeability to toners include denatured products of aniline black and fatty acid metal salts; quaternary ammonium salts such as tributylbenzylammonium-1-hydroxy-4-naphthalenesulfonate and tetrabutylammonium tetrafluoroborate, and their derivatives; onium salts such as phosphonium salts, and lake pigments of these; triphenylmethane dyes and lake pigments thereof (using phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferricyanide or ferrocyanide compounds as laking agents); and metal salts of higher fatty acids.

[0155] The method for producing the toner particles is not particularly limited, and may be a pulverization method or a polymerization method such as an emulsion polymerization method, a suspension polymerization method, or a solution suspension method.

[0156] From the viewpoint of reducing density unevenness during fixing by maintaining viscoelasticity at high temperatures, the pulverization method is preferred because it disperses the components insoluble at high temperatures as a whole throughout the toner. In addition, the toner production method preferably includes a step of melt-kneading the polymer A.

[0157] In the pulverization method, first, the polymer A used to constitute the toner particles is fully mixed with the polymer B, colorant, wax, charge control agent and other additives as required in a mixing device such as a Henschel mixer or a ball mill (mixing step). Then, the resulting mixture is melt-kneaded with a heating and kneading device such as a twin-screw kneading extruder, a heating roller, a kneader or an extruder (melt-kneading step). After cooling and solidification, the melt-kneaded product is pulverized (pulverization step) and classified as required. Thus, toner particles can be obtained.

[0158] Prior to the mixing step, it is preferred to include a step of melt-kneading the polymers A and B while adding a crosslinking agent to crosslink the mixture. Since a part of the binder resin is insoluble at high temperatures, this makes it possible to increase the viscoelasticity at high temperatures.

[0159] The toner particles may be used as a toner as they are. It may also be mixed sufficiently with known additives in a mixing device such as a Henschel mixer to obtain a toner as required.

[0160] Examples of calculation methods and measurement methods of various physical properties of the toner and toner materials in the present invention are described below.

[0161] <Method for measuring the content of monomer units derived from various polymerizable monomers in polymer A>

[0162] The content of monomer units derived from various polymerizable monomers in polymer A is determined by 1 Measured by H-NMR.

[0163] Measuring unit: FT NMR unit JNM-EX400 (JEOL Ltd.)

[0164] Measuring frequency: 400MHz

[0165] Pulse condition: 5.0μs

[0166] Frequency range: 10500Hz

[0167] Cumulative number of times: 64

[0168] Measuring temperature: 30℃

[0169] Sample: prepared by placing 50 mg of a measurement sample in a sample tube having an inner diameter of 5 mm, adding deuterated chloroform (CDCl 3 ) as a solvent, and dissolving the mixture in a constant temperature bath at 40° C.

[0170] In the income 1 From the peaks attributable to the constituent elements of the monomer units derived from the first polymerizable monomer in the H-NMR chart, a peak that is unrelated to the peaks attributable to the constituent elements derived from the other monomer units is selected, and the integral value S1 of the peak is calculated. Similarly, from the peaks attributable to the constituent elements of the monomer units derived from the second polymerizable monomer, a peak that is unrelated to the peaks attributable to the constituent elements derived from the other monomer units is selected, and the integral value S2 of the peak is calculated.

[0171] When the third polymerizable monomer is used, a peak independent of peaks attributable to constituent elements derived from other monomer units is selected from peaks attributable to constituent elements derived from monomer units derived from the third polymerizable monomer, and an integrated value S3 of the peak is calculated.

[0172] The content of the monomer unit derived from the first polymerizable monomer is determined as follows using the integrated values ​​S1, S2, and S3: n1, n2, and n3 are the numbers of hydrogen atoms in the constituent element to which the peak observed in each portion is attributed.

[0173] Ratio of monomer units derived from the first polymerizable monomer (mol%) = {(S1 / n1) / ((S1 / n1)+(S2 / n2)+(S3 / n3)}×100

[0174] The ratio of the monomer units derived from the second polymerizable monomer and the third polymerizable monomer was determined in the same manner as shown below.

[0175] Ratio of monomer units derived from the second polymerizable monomer (mol%) = {(S2 / n2) / ((S1 / n1)+(S2 / n2)+(S3 / n3)}×100

[0176] Ratio of monomer units derived from the third polymerizable monomer (mol%) = {(S3 / n3) / ((S1 / n1)+(S2 / n2)+(S3 / n3)}×100

[0177] When a polymerizable monomer containing no hydrogen atom among its constituent elements other than vinyl is used in the polymer A, 13 C as the measurement kernel 13 C-NMR measurements were performed in single pulse mode and 1 The ratio is calculated in the same manner by H-NMR.

[0178] When the toner is produced by suspension polymerization, independent peaks are not observed due to the overlap of peaks of wax and other resins. Therefore, the ratio of monomer units derived from various polymerizable monomers in polymer A cannot be calculated. In this case, polymer A' is produced by performing similar suspension polymerization without using a release agent or other resins and analyzed as polymer A.

[0179] <Measurement method of storage elastic modulus>

[0180] As measuring unit, an "ARES" rotating plate rheometer (TA Instruments) was used.

[0181] The toner was pressure-molded into a disk shape having a diameter of 8.0 mm and a thickness of 2.0±0.3 mm at 25° C. in a tablet press to be used as a measurement sample.

[0182] The sample is mounted on parallel plates, and the temperature is raised from room temperature (25°C) to 55°C over a 15-minute process to shape the sample, which is then cooled to the initial temperature for viscoelasticity measurement and the measurement is started. It is important here that the sample is set so that the initial normal force is 0. In addition, as described below, the influence of the normal force is also eliminated in subsequent measurements by automatic tension adjustment (Auto Tension Adjustment ON).

[0183] The measurement was performed under the following conditions.

[0184] (1) Use a parallel plate with a diameter of 7.9 mm.

[0185] (2) The frequency is 6.28 rad / sec (1.0 Hz).

[0186] (3) The initial applied strain (Strain) was set to 0.1%.

[0187] (4) The temperature was increased at a rate of 2.0°C / min between 30°C and 200°C. The measurement was performed under the following automatic adjustment mode setting conditions. The measurement was performed in the automatic strain adjustment mode (Auto Strain).

[0188] (5) Set the maximum strain (Max Applied Strain) to 20.0%.

[0189] (6) The maximum torque (Max Allowed Torque) is set to 200.0 g·cm, and the minimum torque (MinAllowed Torque) is set to 0.2 g·cm.

[0190] (7) Set the Strain Adjustment to 20.0% of the Current Strain. Use the Auto Tension mode during the measurement.

[0191] (8) Set Auto Tension Direction to Compression.

[0192] (9) Set the Initial Static Force to 10.0 g and the Auto Tension Sensitivity to 40.0 g.

[0193] (10) The operating condition of Auto Tension is that the sample modulus is 1.0×10 3 Pa or above.

[0194] When a THF-soluble component of the toner is used as a sample, the sample is prepared by the following method.

[0195] 1.5 g of the toner for measuring the storage elastic modulus is accurately weighed, put in a cylindrical filter paper (product name: No. 86R, 28×100 mm, Advantech Toyo Corp.), and placed in a Soxhlet extractor.

[0196] Using 200 mL of tetrahydrofuran (THF) as a solvent, it was extracted for 18 hours at a reflux rate with an extraction cycle of the solvent of about once every 5 minutes.

[0197] After the extraction, THF was removed from the extracted THF solution using an evaporator, and the residue was vacuum dried at 40 °C for 8 hours to obtain a THF-soluble component. Using a tablet press under an environment of 25 °C, the extracted THF-soluble component was press-molded into a disc shape with a diameter of 8.0 mm and a thickness of 2.0 ± 0.3 mm, and used as a sample.

[0198] <Calculation method of SP value>

[0199] SP 12 and SP 22 and SP 32 and SP 42 were determined as follows according to the calculation method proposed by Fedors.

[0200] For atoms or atomic groups in the molecular structure of various polymerizable monomers, the evaporation energy (Δei) (cal / mol) and molar volume (Δvi) (cm 3 / mol) were determined from the table described in "Polym. Eng. Sci., 14(2), 147 - 154(1974)", and (4.184×ΣΔei / ΣΔvi) 0.5 was given as the SP value (J / cm 3 ). 0.5 was given.

[0201] For atoms or atomic groups in the molecular structure of the same polymerizable monomer in which the double bond is broken by polymerization, SP 11 and SP 21 and SP 31 and SP 41 were calculated by a similar method.

[0202] <Measurement method of glass transition temperature Tg>

[0203] The glass transition temperature Tg was measured using a "Q2000" differential scanning calorimeter (TA Instruments) according to ASTM D3418 - 82. The melting points of indium and zinc were used for temperature calibration of the device detection part, and the heat of fusion of indium was used for calibration of the calorific value.

[0204] Specifically, about 2 mg of the sample was accurately weighed and placed in an aluminum pan, and an empty aluminum pan was used as a reference, and the measurement was performed at a temperature increase rate of 10°C / min in the measurement temperature range of -10°C to 200°C. For this measurement, the temperature was first raised to 200°C, then lowered to -10°C, and then raised again. During the second temperature increase, a specific heat change was obtained in the range of 30°C to 100°C. The glass transition temperature Tg is the intersection between the differential thermal curve and a straight line drawn between the midpoints of the baseline before and after the specific heat change.

[0205] <Measurement of Weight Average Molecular Weight Mw (Measurement of Molecular Weight Distribution of THF Soluble Component of Toner)>

[0206] The molecular weight (Mw) of the THF soluble component of the polymer A was measured by gel permeation chromatography (GPC) as follows.

[0207] First, the sample was dissolved in tetrahydrofuran (THF) at room temperature over a 24-hour period. The resulting solution was filtered through a solvent-resistant membrane filter "Maishori Disk" (Tosoh Corp.) with a pore size of 0.2 μm to obtain a sample solution. The concentration of the THF-soluble component in the sample solution was adjusted to about 0.8% by mass. The sample solution was used for measurement under the following conditions.

[0208] System: HLC8120GPC (Detector: RI) (Tosoh Corp.)

[0209] Column: Shodex KF-801, 802, 803, 804, 805, 806, 807 (7 connections) (Showa Denko K.K.)

[0210] ·Eluent: Tetrahydrofuran (THF)

[0211] Flow rate: 1.0mL / min

[0212] Oven temperature: 40.0℃

[0213] Sample injection volume: 0.10mL

[0214] The molecular weight calibration curve prepared using standard polystyrene resin (product name: TSK standard polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500, Tosoh Corp.) is used to calculate the molecular weight of the sample.

[0215] <Method for measuring melting point>

[0216] The melting points of the polymer A, the release agent, etc. were measured using DSC Q1000 (TA Instruments) under the following conditions.

[0217] Heating rate: 10℃ / min

[0218] Measurement start temperature: 20°C

[0219] Measurement end temperature: 180℃

[0220] The melting points of indium and zinc are used for temperature correction of the detection portion of the device, and the heat of fusion of indium is used for correction of the calorific value.

[0221] Specifically, 5 mg of the sample was accurately weighed into an aluminum pan, and differential scanning calorimetry was performed. An empty silver pan was used as a reference.

[0222] The peak temperature of the maximum endothermic peak during the first temperature increase is given as the melting point.

[0223] When there are multiple peaks, the maximum endothermic peak is the peak with the largest endothermic amount.

[0224] <Method for measuring tetrahydrofuran (THF) insoluble components>

[0225] 1.5 g of toner for measuring THF insoluble components (0.7 g when measuring THF insoluble components of a single resin) (W1 g) is accurately weighed, placed in a pre-weighed cylindrical filter paper (product name: No. 86R, 28×100 mm, Advantech Toyo Corp.), and placed in a Soxhlet extractor.

[0226] 200 mL of tetrahydrofuran (THF) was used as a solvent, and the extraction was performed for 18 hours at a reflux rate with an extraction cycle of the solvent being approximately once every 5 minutes.

[0227] After the extraction, the cylindrical filter paper was taken out and air-dried, and then vacuum-dried at 40°C for 8 hours, the mass of the cylindrical filter paper including the extraction residue was accurately weighed, and the weight of the cylindrical filter paper was subtracted to calculate the mass of the extraction residue (W2g).

[0228] Next, the content (W3 g) of components other than the resin component is determined by the following procedure (when the THF-insoluble component of the resin alone is measured, W3 is 0 g).

[0229] About 2 g of toner was accurately weighed (W a g) into a pre-weighed 30 mL magnetic crucible.

[0230] The magnetic crucible was placed in an electric furnace and heated at about 900° C. for about 3 hours, cooled in the electric furnace, and then placed in a desiccator at room temperature to cool for more than 1 hour, and then the mass of the crucible including the residual incineration ash was weighed, and the mass of the crucible was subtracted to calculate the residual incineration ash content (W b g).

[0231] Then, the mass (W3g) of the residual incineration ash in the sample W1g is calculated by the following formula (A).

[0232] W3=W1×(W b / W a ) (A)

[0233] In this case, the THF insoluble component is obtained by the following formula (B).

[0234] THF insoluble component (mass %) = {(W2-W3) / (W1-W3)}×100 (B)

[0235] <Measurement of Endothermic Heat of Tetrahydrofuran-Insoluble Component of Toner>

[0236] The endothermic amount of the tetrahydrofuran-insoluble component of the toner is measured using DSC Q1000 (TA Instruments) under the following conditions.

[0237] Heating rate: 10℃ / min

[0238] Measurement start temperature: 20°C

[0239] Measurement end temperature: 180℃

[0240] The melting points of indium and zinc are used for temperature correction of the detection portion of the device, and the heat of fusion of indium is used for correction of the calorific value.

[0241] Specifically, about 5 mg of the extraction residue described in the method for measuring THF insoluble components is placed in an aluminum pan and subjected to differential scanning calorimetry. An empty silver pan is used as a reference. For this measurement, the temperature is first raised to 200°C, then lowered to 10°C, and then raised again. In the DSC curve obtained from the temperature increase process, the peak top temperature of the maximum endothermic peak in the temperature range of 10°C to 200°C is determined. The endothermic heat (ΔH) of the endothermic peak is the integral value of the endothermic peak.

[0242] Example

[0243] The present invention is described in more detail below using Examples and Comparative Examples, but the present invention is by no means limited to these Examples. Unless otherwise specified, the parts used in the examples are based on mass.

[0244] Preparation Example of Polymer A1

[0245] The following materials were added to a reactor equipped with a reflux condenser, a stirrer, a thermometer and a nitrogen inlet tube in a nitrogen atmosphere.

[0246] Solvent: 100.0 parts of toluene

[0247] Monomer composition: 100.0 parts

[0248] (The monomer composition is a mixture of the following behenyl acrylate, methacrylonitrile and styrene in the following proportions)

[0249] Behenyl acrylate (first polymerizable monomer) 67.0 parts (28.9 mol%)

[0250] Methacrylonitrile (second polymerizable monomer) 22.0 parts (53.8 mol%)

[0251] Styrene (third polymerizable monomer) 11.0 parts (17.3 mol%)

[0252] · tert-Butyl peroxypivalate (Perbutyl PV, NOF Corp.) 3.0 parts

[0253] The reactor contents were stirred at 200 rpm, heated to 70° C., and polymerized for 12 hours to obtain a solution of a polymer of the monomer composition dissolved in toluene. Next, the solution was cooled to 25° C., and added to 1,000.0 parts of methanol under stirring to precipitate a methanol-insoluble component. The resulting methanol-insoluble component was filtered out, washed with methanol, and vacuum dried at 40° C. for 24 hours to obtain polymer A1. The weight average molecular weight of polymer A1 was 20100, the acid value was 0.0 mgKOH / g, and the melting point was 62° C.

[0254] NMR analysis of the polymer A1 showed that it contained 28.9 mol % of monomer units derived from behenyl acrylate, 53.8 mol % of monomer units derived from methacrylonitrile and 17.3 % of monomer units derived from styrene.

[0255] Preparation of monomers having carbamate groups

[0256] 50.0 parts of methanol were charged into the reactor, and then 5.0 parts of KarenzMOI (2-isocyanatoethyl methacrylate, Showa Denko) were added dropwise under stirring at 40° C. After the addition was completed, it was stirred for 2 hours while maintaining the temperature at 40° C. Then, the unreacted methanol was removed in an evaporator to prepare a monomer having a carbamate group.

[0257] Preparation of monomers having urea groups

[0258] 50.0 parts of dibutylamine were charged into a reactor, and then 5.0 parts of KarenzMOI (2-isocyanatoethyl methacrylate, Showa Denko) were added dropwise at 40° C. under stirring. After the addition was completed, it was stirred for 2 hours. Unreacted dibutylamine was then removed in an evaporator to prepare a monomer having a urea group.

[0259] Production Examples of Polymers A2 to A25

[0260] Polymers A2 to A25 were obtained by changing the monomer formulation from the production example of polymer A1 as shown in Table 1. The physical properties of polymers A1 to A25 are shown in Table 2.

[0261] [Table 1]

[0262]

[0263] The abbreviations in Tables 1 and 2 are defined as follows.

[0264] HPMA: 2-Hydroxypropyl Methacrylate

[0265] UT: Monomer with urethane group

[0266] UR: Monomer with urea group

[0267] [Table 2]

[0268]

[0269]

[0270] Preparation Example of Polymer B1

[0271]

[0272] The polyester monomer mixture was charged into a 5-liter autoclave, and 0.05% by mass of tetraisobutyl titanate was added relative to the total amount of the polyester monomer mixture. A reflux condenser, a moisture separator, a nitrogen inlet pipe, a thermometer, and an agitator were installed, and nitrogen was introduced into the autoclave as the polycondensation reaction was carried out at 230°C. The reaction time was adjusted to obtain the molecular weight shown in Table 4. After the reaction was completed, the contents were taken out of the container, cooled, and pulverized to obtain polymer B1. The weight average molecular weight of the obtained polymer B1 was Mw45,000, and Tg was 62°C.

[0273] Preparation Examples of Polymers B2 to B5

[0274] Polymers B2 to B5 were obtained by changing the monomer formulation from the production example of polymer B1 as shown in Table 3. The physical properties of polymers B2 to B5 are shown in Table 4.

[0275] [Table 3]

[0276]

[0277] [Table 4]

[0278]

[0279] Preparation Example of Polymer B6

[0280]

[0281] These polyester monomers were charged into a four-necked flask, a pressure reducer, a moisture separator, a nitrogen introduction device, a thermometer and an agitator were installed, and the mixture was stirred at 160°C in a nitrogen atmosphere. Then, a mixture of 40 parts of vinyl polymer monomers (styrene: 60.0 parts, 2-ethylhexyl acrylate: 40.0 parts) for constituting the vinyl polymer part and 2.0 parts of benzoyl peroxide as a polymerization initiator was added dropwise through a dropping funnel over a 40-hour process. Then, it was reacted at 160°C for 5 hours, the temperature was raised to 230°C, 0.05% by mass of tetraisobutyl titanate was added, and the reaction time was adjusted to obtain the molecular weight shown in Table 4. After the reaction was completed, the reactant was taken out of the reactor, cooled, and crushed to obtain polymer B6. The physical properties of the obtained polymer B6 are shown in Table 4.

[0282] Preparation Example of Polymer B7

[0283]

[0284] These polyester monomers were charged into a four-necked flask, a pressure reducer, a moisture separator, a nitrogen introduction device, a thermometer and an agitator were installed, and the mixture was stirred at 160°C in a nitrogen atmosphere. Then, a mixture of 40 parts of vinyl polymer monomers (styrene: 60.0 parts, 2-ethylhexyl acrylate: 40.0 parts) for constituting the vinyl polymer part and 2.0 parts of benzoyl peroxide as a polymerization initiator was added dropwise through a dropping funnel over a 40-hour process. Then, it was reacted at 160°C for 5 hours, the temperature was raised to 230°C, 0.05% by mass of tetraisobutyl titanate was added, and the reaction time was adjusted to obtain the molecular weight shown in Table 4. After the reaction was completed, the reactant was taken out of the reactor, cooled, and crushed to obtain polymer B7. The physical properties of the obtained polymer B7 are shown in Table 4.

[0285] Preparation Example of Polymer B8

[0286] 300 parts of xylene were charged into a 4-necked flask, the inside of the container was sufficiently purged with nitrogen under stirring, and the temperature was raised to reflux.

[0287] ·Styrene 78.0 parts

[0288] · 21.0 parts of n-butyl acrylate

[0289] ·Divinylbenzene 1.0 part

[0290] The above mixture was added dropwise under reflux over a 4-hour process, and maintained for 2 hours to complete polymerization and obtain a solution of polymer B8. From the solution, an organic solvent was distilled off, and the resulting resin was cooled and solidified, then pulverized to obtain polymer B8. The physical properties of polymer B8 are shown in Table 4.

[0291] Preparation Example of Polymer A26

[0292] Polymer A1: 70.0 parts

[0293] Polymer B1: 30.0 parts

[0294] These materials were premixed in an FM mixer (Nippon Coke & Engineering) and fed to a twin-screw extruder (Ikegai Iron Works, PCM-30) at a rate of 10 kg / hour. At the same time, tert-butyl peroxypivalate (Perbutyl PV, NOF Corp.) was fed at a rate of 0.20 kg / hour for crosslinking reaction. The resulting resin was cooled, solidified, and then pulverized to obtain polymer A26.

[0295] Preparation Example of Polymer A27

[0296] In the production example of polymer 26, polymer A5 was used instead of polymer A1 to obtain polymer A27.

[0297] Preparation Example of Polymer A28

[0298] In the production example of polymer 26, polymer A6 was used instead of polymer A1 to obtain polymer A28.

[0299] Production Example of Toner Particles 1

[0300]

[0301] These materials were premixed in an FM mixer (Nippon Coke & Engineering) and then melt-kneaded in a twin-screw extruder (Ikegai Iron Works, PCM-30).

[0302] The obtained kneaded product was cooled, coarsely pulverized in a hammer mill, and then pulverized in a mechanical pulverizer (Turbo Kogyo T-250), and the obtained finely pulverized powder was classified with a multi-classifier using the Coanda effect to obtain negatively charged colorant particles 1 having a weight average particle size (D4) of 7.5 μm.

[0303] Production Example of Toner 1

[0304] Toner particles 1: 100 parts

[0305] Hydrophobic silica fine powder (number average particle size of primary particles: 10 nm, BET specific surface area of ​​original silica: 200 m 2 / g) 1 part

[0306] These materials were externally added and mixed in an FM mixer (Nippon Coke & Engineering) to obtain Toner 1. The physical properties of Toner 1 are shown in Table 5.

[0307] Production Examples of Toners 2 to 32

[0308] Toner particles 2 to 32 were obtained by changing the materials used in the production example of toner particle 1 as shown in Table 6. Then, toner particles 2 to 32 were obtained in the same manner as in the production example of toner 1 except that the toner particles were changed.

[0309] [Table 5]

[0310]

[0311] [Table 6]

[0312]

[0313] In the table, Mo means "magnetic iron oxide", and CB means "carbon black". The amounts of materials in the table represent parts.

[0314] Preparation Examples of Comparative Toners 1 to 7

[0315] Comparative toner particles 1 to 7 were obtained by changing the materials used in the production example of toner particle 1 as shown in Table 6. Then, comparative toner particles 1 to 7 were obtained in the same manner as in the production example of toner 1 except that the toner particles were changed.

[0316] Example 1

[0317] The evaluation apparatus used in these examples was a commercially available HP LaserJet Enterprise M609dn magnetic single component printer (Hewlett Packard: process speed 420 mm / s). This printer was used to evaluate Toner 1 as follows. Vitality (Xerox, basis weight 75 g / cm 2 The evaluation results are shown in Table 7.

[0318] Examples 2 to 32

[0319] Evaluation was performed in the same manner as in Example 1 using Toners 2 to 32. Since Toner 23 is not magnetic, it was evaluated using a Color Laser Jet CP4525 commercially available color printer (HP).

[0320] Comparative Examples 1 to 7

[0321] Evaluation was performed in the same manner as in Example 1 using Comparative Toners 1 to 7. The evaluation results of Comparative Toners 1 to 7 are shown in Table 7.

[0322] Evaluation of low temperature fixability

[0323] In order to evaluate the low temperature fixability, the fixing unit was taken out from the modified evaluation apparatus, which was modified so that the temperature could be set arbitrarily, and given a process speed of 520 mm / sec, to obtain a modified external fixing unit. Using this unit, the temperature was controlled in increments of 5°C within a temperature range of 120°C to 180°C, and a halftone image having an image density of 0.60 to 0.65 was output. The resulting image was rubbed back and forth 5 times with Silbon paper under a load of 4.9 kPa, and the image density reduction rate before and after rubbing was measured.

[0324] The set temperature of the fixing unit is plotted on the horizontal axis, and the density reduction rate is plotted on the vertical axis of the coordinate plane, all points are connected with straight lines, and the low-temperature fixability is evaluated according to the following criteria when the fixing temperature of the fixing unit when the image density reduction rate is 10% is given as the fixing start temperature of the colorant. The low-temperature fixability evaluation is performed under a low-temperature, low-humidity environment (7.5°C / 15%RH) that is unfavorable for heat-fixing colorants. Scores above C are considered good.

[0325] Evaluation criteria

[0326] A: The fixing start temperature is less than 145°C

[0327] B: Fixing start temperature is 145°C or higher and less than 150°C

[0328] C: Fixing start temperature is 150°C or higher and less than 155°C

[0329] D: Fixing start temperature is 155℃ or above

[0330] Evaluation of image non-uniformity

[0331] 100 whole solid images were continuously output as sample images under normal temperature and humidity environment (23°C, 60%RH), and the last 5 were taken out. 9 points were equally selected from the total solid image density of the obtained image, and the reflection density was measured using a Macbeth reflection densitometer with an SPI filter. The difference was calculated from the maximum and minimum values ​​of the 9 points, and the image unevenness during fixing was evaluated based on the average difference of the 5 sheets. Scores above C were considered good.

[0332] Evaluation criteria

[0333] A: less than 0.04

[0334] ·B: 0.04 or more and less than 0.06

[0335] ·C: 0.06 or more and less than 0.08

[0336] D: 0.08 or more

[0337] Evaluation of initial development properties

[0338] Five whole solid images were output as sample images under normal temperature and humidity environment (23°C, 60% RH). The reflection density of one point in the center of the obtained whole solid image was measured using a Macbeth densitometer using an SPI filter, and the initial developability was evaluated based on the average density of the five images. Scores above C were considered good.

[0339] Evaluation criteria

[0340] ·A: 1.25 or more

[0341] B: 1.15 or more and less than 1.25

[0342] C: 1.05 or more and less than 1.15

[0343] D: less than 1.05

[0344] Evaluation of storage

[0345] 10 g of the toner was weighed into a 50 mL resin cup and placed in each of 6 thermostatic baths with a temperature difference of 2° C. starting from 50° C. for 3 days. After 3 days, the toner was visually observed, and the storage property was evaluated based on the highest temperature at which the toner lumps became smaller and broke when the cup was rotated. Scores of C or above were considered good.

[0346] Evaluation criteria

[0347] ·A: Above 58℃

[0348] B: 54°C or higher and less than 58°C

[0349] C: 50℃ or higher and less than 54℃

[0350] D: less than 50℃

[0351] [Table 7]

[0352]

[0353] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.

Claims

1. A toner comprising toner particles containing a binder resin, characterized in that: The storage elastic modulus Gt'(150) of the toner at 150°C is 1.0×10 4 Pa or above, The binder resin includes a polymer A which is a polymer of a composition including a first polymerizable monomer and a second polymerizable monomer different from the first polymerizable monomer, The first polymerizable monomer is selected from 18-36 At least one of the group consisting of alkyl (meth)acrylates, The composition further includes a third polymerizable monomer different from the first polymerizable monomer and the second polymerizable monomer, The third polymerizable monomer is at least one selected from the group consisting of styrene, methyl methacrylate and methyl acrylate, The content of the first polymerizable monomer in the composition is 5.0 mol% to 60.0 mol% of the total moles of all polymerizable monomers in the composition. The content of the second polymerizable monomer in the composition is 20.0 mol% to 95.0 mol% of the total moles of all polymerizable monomers in the composition. The SP value of the first polymerizable monomer is SP 12 (J / cm 3 ) 0.5 , the SP value of the second polymerizable monomer is SP 22 (J / cm 3 ) 0.5 , and satisfies the following formula (2): 0.60 ≤ (SP 22 -SP 12 ) ≤ 15.00 (2), The SP value of each of the first polymerizable monomer and the second polymerizable monomer=(4.184×ΣΔei / ΣΔvi) 0.5 , Δei represents the evaporation energy of the atoms or atomic groups in the molecular structure of each of the first polymerizable monomer and the second polymerizable monomer in units of cal / mol, and Δvi represents the evaporation energy of the atoms or atomic groups in the molecular structure of each of the first polymerizable monomer and the second polymerizable monomer in units of cm 3 / mol, and The content of the polymer A in the binder resin is 40% by mass to 100% by mass. 2 . The toner according to claim 1 , wherein the content of the polymer A in the binder resin is 50% by mass to 90% by mass. 3 . The toner according to claim 1 , wherein the binder resin comprises a polymer B different from the polymer A, and the polymer B comprises a polyester resin having a monomer unit derived from a polyhydric alcohol and a monomer unit derived from a polycarboxylic acid.

4. The toner according to claim 1, wherein the binder resin comprises a polymer B different from the polymer A, The polymer B comprises a polyester resin having a monomer unit derived from a polyol and a monomer unit derived from a polycarboxylic acid, and When the SP value of the polycarboxylic acid is SP 42 (J / cm 3 ) 0.5 When , the following formula (4) is satisfied: 0.0 ≤ |(SP 42 -SP 22 )| ≤ 5.0 (4), The SP value of the polycarboxylic acid = (4.184 × ΣΔei / ΣΔvi) 0.5 , Δei represents the evaporation energy of the atoms or atomic groups in the molecular structure of the polycarboxylic acid in units of cal / mol, and Δvi represents the evaporation energy of the atoms or atomic groups in the molecular structure of the polycarboxylic acid in units of cm 3 / mol molar volume.

5. The toner according to claim 1, wherein the second polymerizable monomer is at least one selected from the group consisting of the following formulae (A) and (B): in, In the formula (A), X represents a single bond or C 1-6 Alkylene, and R 1 Indicates nitrile group -C≡N, Amino-C(=O)NHR 10 , where R 10 A hydrogen atom or C 1-4 alkyl, Hydroxyl, -COOR 11 , where R 11 C 1-6 Hydroxyalkyl, Urea-NH-C(=O)-N(R 13 )2, where each R 13 are independently hydrogen atoms or C 1-6 Alkyl, -COO(CH2)2NHCOOR 14 , where R 14 C 1-4 Alkyl, or -COO(CH2)2-NH-C(=O)-N(R 15 )2, where each R 15 are independently hydrogen atoms or C 1-6 Alkyl, and R 3 is a hydrogen atom or a methyl group, and In the formula (B), R 2 C 1-4 Alkyl, and R 3 A hydrogen atom or a methyl group. 6 . The toner according to claim 1 , wherein in measurement of molecular weight distribution of a tetrahydrofuran-soluble component of the toner, a weight average molecular weight is 30,000 or more.

7. The toner according to claim 1, wherein in the viscoelasticity measurement of the tetrahydrofuran-soluble component of the toner, the storage elastic modulus Gk'(50) at 50° C. and the storage elastic modulus Gk'(100) at 100° C. satisfy the following formulas (5) and (6): Gk'(50) ≥ 1.0×10 7 For (5) Gk'(100) ≤ 1.0×10 4 Pa (6)。 8 . The toner according to claim 1 , wherein an endothermic amount in DSC measurement of a tetrahydrofuran-insoluble component of the toner is 4.0 J / g or less.

9. The toner according to claim 1, wherein the toner is a pulverized toner.

10. The method for producing a toner according to any one of claims 1 to 9, characterized in that: The method comprises the step of melt-kneading the polymer A.